The unresolved - Welsh, T. K. (New York : Dutton Children's Books, 2006)
In 1904 New York City, the spirit of a deceased German American teenage girl searches for the person responsible for the Slocum steamboat fire that claimed her life and the lives of more than 1000 other passengers.
Keywords: General Slocum (Steamboat) -- Juvenile fiction; Fires -- New York (State) -- New York -- Fiction; Shipwrecks -- Juvenile fiction; Ghosts -- Juvenile fiction; German Americans -- Juvenile fiction; New York (N.Y.) -- History -- 1898-1951 -- Juvenile fiction